Accident causation factors, risky driving behaviour and road safety management toward road accidents - Harith, Siti Hawa (2020)
Road accident involving young drivers and riders in Malaysia is increasing over the years, contributing to the loss of lives and property. In order to address this issue, the contributing factors that include five individual factors (drivers’ attitude, moral norm, perceived behavioural control (PBC), sensation seeking, past behaviour) and one social factor (group norm) were investigated. This study seeks to answer several gaps. Firstly, a practical-knowledge gap which has been identified through the failure of Road Safety Plan 2014 - 2020 policy. Secondly, evidence gap which has been identified through the conceptualization of two moderators of soft and hard approaches. Thirdly, empirical gap which has been identified through the development of the conceptual framework that combined six independent variables: attitude, moral norm, PBC, sensation seeking, past behaviour and group norm, a mediator of risky driving behaviour, moderators of soft and hard approaches and dependent variable of accident involvement among young drivers and riders. Finally, theoretical gaps which have been identified through the underpinning theories of Attribution Theory, Fear Appeal Theory and Reinforcement Theory. The respondents of this study were young drivers and riders aged between 18 to 25 years old who had experienced a road accident for the past 12 months, possessed a valid driving license with at least six months of experience and remain active drivers or riders. This quantitative study was undertaken in Selangor, Johor and Kuala Lumpur (states with the highest accident number for 10 consecutive years). Results showed that all the independent variables significantly influence risky driving behaviour and accident among young drivers and riders except for the group norm. Whereas for the mediating analysis, both moral norm and group norm were reported to be insignificant, which means that although the variables could lead toward the occurrence of risky driving behaviour, such behaviour did not necessarily cause road accident among young drivers and riders. Finally, for the moderating analysis, only soft approach was reported to be significant to overcome the accident involvement issue among young drivers and riders. This result is also consistent with report released by Malaysian Institute of Road Safety and Research (MIROS) which reported that Malaysian citizens neglect traffic rules and regulations. These findings help to enrich the body of knowledge on accident involvement among young drivers and riders, especially in the context of Asian countries particularly Malaysia. The result also proved that the best way to overcome accident among young drivers and riders is to intervene through the soft approach.